Performance of LV vacuum contactors with condensed composite multicomponent contacts - Miedzinski, B.; Okraszewski, Z.; Grechanyuk, M.; Kozlowski, A.; Grodzinski, A. (Электрические контакты и электроды, 2010)
Paper presents and discusses the investigated results of LV vacuum contactors with contacts made of selected condensed composite materials under both rated and short circuit conditions of operation.